Interpretasi Pemuda Muslim terhadap Kajian Dakwah Menggunakan Komunikasi Virtual - Kurnia Nur Fitriyani; Deden Mauli Darajat (Lembaga Pengembangan Kinerja Dosen, 2026)
The era of globalization and the rapid advancement of information technology have transformed the landscape of dakwah (Islamic propagation), shifting from conventional pulpits to virtual communication platforms (social media, podcasts, streaming). This transition, in line with the Diffusion of Innovation Theory, enables Islamic messages to reach a broad audience without geographical boundaries. Digital dakwah is highly relevant and urgent to research given the dominant use of social media by Muslim Youth, a group that seeks attention but also possesses a tendency toward critical thinking. This research has a dual aim: (1) to analyze the Interpretation of Muslim Youth towards virtual dakwah studies, and (2) to analyze the Effectiveness of Implementing Dakwah Studies through social media platforms. The accessibility of fragmented and competitive content makes the interpretation process active and crucial, where youth are no longer passive recipients but choose sources based on algorithms and their own interests. This study uses the Constructivism Paradigm to understand a dynamic and complex social reality, employing a Descriptive Qualitative Approach and the Online Ethnography Method. Data is collected through Observation, Interviews, and Documentation, with Data Triangulation (source, technique, and time) to ensure the validity of the findings. Social media holds great potential as an effective and inclusive dakwah tool. However, the effectiveness of its expansion must be balanced with the quality of the content and the capacity of Muslim Youth to perform critical, contextual, and responsible interpretation.